Efficacy and safety analysis of treatment in patients with EGFR-mutated advanced NSCLC who progressed on TKIs: a systematic review and meta-analysis - Zhang, Shuang; Li, Rixin; Cui, Heran; Li, Hui (Frontiers in Immunology, 2025)
BackgroundThe treatment of patients with advanced epidermal growth factor receptor (EGFR)-mutated non-small-cell lung cancer (NSCLC) whose disease progresses after tyrosine-kinase inhibitors (TKIs) treatment has become a research hotspot.ObjectiveTo identify effective and safe treatment options for patients with EGFR-mutated advanced NSCLC who progressed on TKIs.MethodsWe searched databases including PubMed, Cochrane Library, and major international conference abstracts (2018–2023) to identify phase II/III randomized controlled trials (RCTs) and single-arm studies of EGFR-mutated advanced NSCLC post-TKI progression from April 2018 to June 2024. Outcomes included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and grade ≥3 adverse events (AEs), treatment-related AEs (TRAEs), and TRAE-related deaths. Bayesian network meta-analysis and individual patient data (IPD) meta-analysis were performed to compare treatment efficacy and safety.ResultsThis meta-analysis included randomized controlled trials (RCTs) and 5 single-arm phase 2 trials (3116 patients) evaluating 7 treatment regimens for EGFR-mutated advanced NSCLC post-TKI progression. In the network meta-analysis (NMA), amivantamab plus lazertinib plus chemotherapy (amiva-lazer-chemo) yielded the highest PFS (surface under the cumulative ranking curve [SUCRA]: 0.88; hazard ratio [HR] vs chemotherapy, 0.44; 95% CI, 0.32-0.61), followed by AK112 plus chemotherapy (SUCRA: 0.79; HR, 0.46; 95% CI, 0.32-0.67). All regimens significantly improved PFS compared with chemotherapy alone. Amivantamab plus chemotherapy ranked highest for ORR (SUCRA: 0.82; odds ratios [OR] vs chemotherapy, 3.16; 95% CI, 1.09-9.41). Amiva-lazer-chemo had the highest grade ≥3 AE incidence. IPD analysis confirmed superior PFS for amiva-lazer-chemo (median, 8.45 months; 95% CI, 7.02-9.26; HR vs chemotherapy, 0.47; 95% CI, 0.40-0.55; P <.001). Moderate ORR heterogeneity (I² = 52.2%) and high AE heterogeneity (I² = 79.5%-92.1%) were noted.ConclusionIn this meta-analysis of patients with TKI-resistant EGFR-mutated advanced NSCLC, the amiva-lazer-chemo regimen was associated with longer PFS at both the study level and individual patient level. Combination therapy with anti-angiogenic agents also represents a viable treatment strategy for this patient population.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024565403.